Septoriablotch epidemic process on spring wheat varieties - E. Yu. Toropova; O. A. Kazakova; V. V. Piskarev (Вавиловский журнал генетики и селекции)
The Septoriablotch of spring wheat leaves and ears is one of the most economically significant infections in the Siberian region. In the control systems of Septoriablotch the main ecologically safe element is resistant  varieties, which are designed to slow down the pathogens reproduction rate and slow down or stop the development of the epiphytotic process. The purpose of the work was to clarify the species composition of Septoriablotch  pathogens for West Siberian regions and spring wheat varieties, to study the epiphytotic process of Septoriadifferentially on the leaves and ears of varieties, and to evaluate the activity of seed transmission of Parastagonospora  nodorum. Studies were carried out in 2016–2018 according to generally accepted methods. Septorialeaf and ear  blotch of spring wheat is widespread in West Siberia and the Trans-Urals, causing a decrease in yield by up to 50 %  or more with the deterioration in grain quality. The causative agents of the disease are P. nodorum, Septoria tritici,  and P. avenaef. sp. triticae, and the species ratio varied across the regions and varieties, and within plant organs.  In Novosibirsk Region, P. nodorumcompletely dominated; S. triticiwas 13.8 times less common; and P. avenae f. sp. triticaewas a singleton. In Tyumen Region, the dominance of P. nodorumwas disrupted in some geographic  locations by S. triticiand P. avenaef. sp. triticae. In Altai Krai, P. nodorumpredominated at all points studied; S. tritici and P. avenaef. sp. triticaewere found everywhere, but 5.6 and 8.6 times less often, respectively. The study of spring  wheat varieties of different origins has not revealed any samples immune to Septoriablotch. A differen tiated manifestation of resistance to Septorialeaf and ear disease has been established. Some varieties show complex resistance, combining reduced susceptibility to Septorialeaf and ear disease. Seed infection with P. nodorumin the  regions of Siberia reached 7 thresholds and was largely (52.5 %) determined by the August weather conditions.  The study of the collection of spring wheat varieties from three Siberian regions has revealed the following trend.  Transmission of P. nodorumwith the seeds of varieties was the most active (7.6 %) in Novosibirsk Region and somewhat weaker in Omsk Region (5.7 %). The most favorable phytosanitary situation was in Kurgan Region, where  varieties transmitted P. nodorumto a low degree (2.1 %), below the threshold.